2018
DOI: 10.14744/less.2018.87609
|View full text |Cite
|
Sign up to set email alerts
|

Direct Trocar Entry For Laparoscopy Safety and Efficiency

Abstract: Introduction: This study is an examination of the safety and efficiency of the direct trocar entry method used to create pneumoperitoneum in laparoscopic surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 7 publications
1
3
0
Order By: Relevance
“…Whereas when the supra umbilical incision was used, the skin incision often needed to be extended just to reach the fascia. This is similar to several studies which report that the open method is safer to practice (Ulusoy, 2018). In a cohort study showing injuries caused by closed techniques (veress needle) for the creation of pneumoperitoneum, the incidence of vascular injuries was 0.018 and visceral injuries was 0.0024 (De Azevedo et al, 2006).…”
Section: Discussionsupporting
confidence: 86%
“…Whereas when the supra umbilical incision was used, the skin incision often needed to be extended just to reach the fascia. This is similar to several studies which report that the open method is safer to practice (Ulusoy, 2018). In a cohort study showing injuries caused by closed techniques (veress needle) for the creation of pneumoperitoneum, the incidence of vascular injuries was 0.018 and visceral injuries was 0.0024 (De Azevedo et al, 2006).…”
Section: Discussionsupporting
confidence: 86%
“…Muneer imran reported just two complications port site hematoma 2% and port site infection 3% 13 . In another study only skin bleeding and ecchymosis was observed in 0.34% cases 22 .…”
Section: Discussionmentioning
confidence: 85%
“…In the study of Karthik et al, the incidence of trocar entry site bleeding was reported as 0.7%. [17] On the other hand, hematoma/ecchymosis rate after DTT was 0.36% in the study of Ulusoy et al [18] Bleeding at the first port of entry is mostly associated with tissue damage resulting from repeated attempts. On the other hand, it is recommended that trocars be placed under direct vision by illuminating the abdominal wall (transillumination), since trocar entry site bleeding is often caused by injury to the epigastric vessels at the secondary trocar entry.…”
Section: Discussionmentioning
confidence: 99%